Application of Constructive Models to Increase The Writing Skills of Grade VI of Elementary School Students - Cahya, Otong; Muharam, Agus; Sujana, Atep; SOpandi, Wahyu; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The low ability of students to write speech scripts will affect the ability of students to communicate formally in speech. Speech is the ability to communicate in front of many people who demand the ability to use language that is good and right, so that the purpose of speech or communication will succeed optimally. This classroom action research aims to improve the ability to write speech texts for grade VI elementary school students through the application of the constructivist model. This research was conducted in two cycles in which each cycle consisted of four activities, namely planning (plan), implementation (act), observation (observeb) and reflection (reflection). The subjects in this study were 15 students from grade VI. Data is collected through tests, observations, and field notes. Data analysis was performed in a descriptive quantitative manner. The results of the study in the first cycle showed an average of 80.7 and in the second cycle showed an average of 96.4 and in this second cycle the percentage of students completeness reached 100% seen from the minimum completeness criteria (KKM) set of 60. With thus the application of the constructivism model can improve the ability to write speech texts for Grade VI students